One-step coagulation to construct durable anti-fouling and antibacterial cellulose film exploiting Ag@AgCl nanoparticle- triggered photo-catalytic degradation. (1st February 2018) - Zhang, Xiaomin; Shu, You; Su, Shengpei; Zhu, Jin
Highlights: Cellulose-Ag@AgCl film have been fabricated by one step coagulation. Ag@AgCl stably embedded in matrix could be attained on condition of 1wt% PVP. The composite film has during antifouling and antibacterial ability. Abstract: An anti-fouling and antibacterial surface of cellulose film was obtained by one-step coagulation of the cellulose-LiCl/Dimethyl acetamide (DMAc) solution with AgNO3 and polyvinyl pyrrolidone (PVP). The AgCl nanocrystals were embedded on the surface of cellulose film with the assistance of PVP, and the Ag@AgCl was formed due to the partly decomposition of AgCl under the visible-light irradiation. Morphology and size of the Ag@AgCl in cellulose matrix could be regulated by changing the concentration of PVP. From a series of comparative tests, Ag@AgCl could be stably embedded on cellulose film at the concentration of 1 wt% PVP, and its photo-degradation efficiency could be still retained 89% after 5-cycle testing. Meanwhile, a dramatic reduction in viable bacteria was also observed within 120 min of exposure on this film, and when exposure time was 180 min, no active bacteria was observed.This work provided a simple pathway to construct the functional cellulose film which could be applied as packaging materials.